On the Sustainable Nexus between Oil Prices and Aviation Stocks - Arif Billah Dar (Sustainable Operations and Computers, 2022)
Aviation stock sensitivity to crude oil prices has raised a suspicion of nexus between aviation stocks and crude oil prices. In this paper, the sustainable nexus between oil Prices and aviation stocks in India are analysed. In particular, it is tested whether there is any sustainable long-term co-movement between the stocks of three aviation companies listed on the Indian stock market and crude oil. The oil prices and aviation stocks are decomposed into different time horizons using the methodology of wavelets. The nexus is studied at shorter, medium, and longer time horizons. Broadly, results show that there is some nexus in the short-run, however, sustainable long-run nexus is missing. The results are found to be robust and approximately similar when data from three Indian aviation stocks are used. It is inferred that sustainable long-run movements in aviation stocks should be attributed to the reasons not related to crude oil price changes.